Evaluating the Real-World Efficacy and Safety of Intravitreal Faricimab in the Management of Neovascular Age-Related Macular Degeneration: A Systematic Review - Barus, Dany Petra Pranata; Adriono, Gitalisa Andayani (International Journal of Retina, 2025)
Introduction: Neovascular age-related macular degeneration (nAMD) is a leading cause of irreversible vision loss in the elderly. Intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapies have revolutionized the treatment of nAMD. Faricimab, a novel bi-specific anti-VEGF and anti-angiopoietin-2 antibody, has shown promise in clinical trials. This comprehensive systematic review aims to evaluate the real-world efficacy and safety of intravitreal faricimab in the management of nAMD. Methods: A comprehensive search was conducted in major electronic databases to identify studies reporting outcomes related to faricimab treatment for nAMD in real-world settings. A total of 6 studies were included, comprising 800 patients including 874 eyes. The primary outcomes of interest included visual acuity improvements, central subfield thickness of retina, and safety. Result: The review reveals that intravitreal faricimab is associated with significant visual acuity improvements in patients with nAMD, with outcomes comparable to or better than existing anti-VEGF agents. Furthermore, patients receiving faricimab typically required fewer injections, resulting in a potentially lower treatment burden. The findings also suggest that faricimab may offer a longer treatment interval, which could have a positive impact on patient quality of life. Conclusion: Regarding safety, faricimab demonstrated a favorable safety profile in the real-world setting, with a low incidence of ocular and systemic adverse events. This suggests that faricimab is well-tolerated by patients, supporting its long-term use in the management of nAMD.